The effect of entrepreneurial leadership, organizational culture and information system on the implementation of risk management - Inayah Syahwani, Asty Khairi (Faculty of Economics and Business Mulawarman University, 2019)
This paper studies the influence entrepreneurial leadership, organizational culture and information systems on the implementation of risk management. This research used quantitative methods by conducting a survey to distribute questionnaires to research objects and processing data using Partial Least Square (PLS). Results from the test using Partial Least Square (PLS) confirm that a company always need a leader who creates opportunities and develops human resources. Organizational culture tends to make progress for the implementation of risk management is supported by a good information system. The results of this study suggest that facing an external environment that can increase the risk of companies required entrepreneurial leaders who provide direction and motivation to employees. In addition, organizational culture that focuses on the external environment, dare to innovate and do the differentiation. There are two culture in professional organizational culture, adhrocracy culture and market culture. Therefore, information systems that owned by company must follow the current technology developments.This study wants to see how the implementation of risk management in a company by assessing the characteristics of organization and knowing the development of the company in innovation with the challenges in the existing environment.